Effects of Nutrient on Algae Biomass during Summer and Winter in Inflow Rivers of Taihu Basin, China. (1st July 2016) - Wu, Pan; Qin, Boqiang; Yu, Ge; Deng, Jianming; Zhou, Jian
ABSTRACT: : To explore the linkage of phosphorus (P), nitrogen (N) and phytoplankton during the summer and winter in the inflow rivers of the Taihu Basin, China, 51 main rivers were investigated in 2013 and 2014. The results showed that high P and N input deteriorated the water quality, and P primarily limited Chlorophyll a concentrations. Diatoms, green algae, and cyanobacteria were the dominant phyla, totaling 29 and 41 species in summer and winter, respectively. Total P negatively affected the phytoplankton diversity during summer and had a stronger positive relationship with richness than total N during winter. The P level restricted the biomass of dominant algae, and turbidity had a greater interaction with cyanobacteria. This study suggests that P drives the phytoplankton assemblages under N‐rich environments in the inflow rivers during summer and winter, indicating the need for nutrient reduction and further monitoring of the rivers to improve the water ecology.